A Critical Assessment of Select Editorial Opinions in The Yoruba News - Taiwo Olunlade (Yoruba Studies Review)
The emergence of new technologies could not have come at a more auspicious moment, for we learn early everything we know about the world around us through one form of the media or another. Before the advent of this impressive array of media technology, information dissemination was limited to the newspaper, radio, or television. Newspapers, in particular, were in vantage position at molding public opinion and creating mass sensibilities on almost every imaginable issue. Tis was also the case with The Yoruba News, printed and published by D. A. Obasa in Ibadan, especially through its editorial opinions for over two decades from 1924-1945. Tis essay is an attempt to revisit selected editions of the newspaper for critical re-assessment of the editorial opinions as regards topical issues of that period.